Evidence of AlII Radical Addition to Benzene. (17th February 2023) - Mandal, Debdeep; Demirer, T. Ilgin; Sergeieva, Tetiana; Morgenstern, Bernd; Wiedemann, Haakon T. A.; Kay, Christopher W. M.; Andrada, Diego M.
Abstract: Electrophilic Al III species have long dominated the aluminum reactivity towards arenes. Recently, nucleophilic low‐valent Al I aluminyl anions have showcased oxidative additions towards arenes C−C and/or C−H bonds. Herein, we communicate compelling evidence of an Al II radical addition reaction to the benzene ring. The electron reduction of a ligand stabilized precursor with KC8 in benzene furnishes a double addition to the benzene ring instead of a C−H bond activation, producing the corresponding cyclohexa‐1, 3(orl, 4)‐dienes as Birch‐type reduction product. X‐ray crystallographic analysis, EPR spectroscopy, and DFT results suggest this reactivity proceeds through a stable Al II radical intermediate, whose stability is a consequence of a rigid scaffold in combination with strong steric protection. Abstract : The electron reduction of diamido‐naphthyl aluminum iodide in benzene produces dialuminyl substituted Birch‐type reduction product. Time dependent EPR experiments in combination with DFT calculations suggest a reaction mechanism where stable Al II radical intermediates play a crucial role for the reaction outcome. The aluminum radical stability is a consequence of a rigid supporting ligand with silyl protective substituents.